Fate of antibiotic resistance genes and metal resistance genes during thermophilic aerobic digestion of sewage sludge. (February 2018) - Jang, Hyun Min; Lee, Jangwoo; Kim, Young Beom; Jeon, Jong Hun; Shin, Jingyeong; Park, Mee-Rye; Kim, Young Mo
Graphical abstract: Highlights: Changes in ARGs, MRGs and intI 1 were investigated during TAD of sewage sludge. Significant decreases in ARGs, MRGs and intI 1 genes were observed in TAD. Shifts in temperature were responsible for changes in ARGs. A decline in bacterial diversity resulted in decrease in resistome during TAD. Abstract: This study examines the fate of twenty-three representative antibiotic resistance genes (ARGs) encoding tetracyclines, sulfonamides, quinolones, β-lactam antibiotics, macrolides, florfenicol and multidrug resistance during thermophilic aerobic digestion (TAD) of sewage sludge. The bacterial community, class 1 integrons ( intI 1) and four metal resistance genes (MRGs) were also quantified to determine the key drivers of changes in ARGs during TAD. At the end of digestion, significant decreases in the quantities of ARGs, MRGs and intI 1 as well as 16S rRNA genes were observed. Partial redundancy analysis (RDA) showed that shifts in temperature were the key factors affecting a decrease in ARGs. Shifts in temperature led to decreased amounts of ARGs by reducing resistome and bacterial diversity, rather than by lowering horizontal transfer potential via intI 1 or co-resistance via MRGs.